A study on legal issues related to blogs businesses in Malaysia: a proposal for a regulatory framework - Mohamed, Duryana; Abdul Ghani Azmi, Ida Madieha; Abdul Ghadas, Zuhairah Ariff (2013)

(untitled)
In the millennium era, the mechanisms of trading has being expanded to include online shopping and internet businesses whereby customers merely browse through the internet to find things they need rather than physically going to the shops. Today, it is also common to find businesses being conducted through blogs, particularly the free lance or those who initially plan doing business just for fun but later gets into a bigger and more serious transactions. Businesses like selling homemade chocolate, cup cakes, designed and personal accessories are among the many types of businesses which are commonly carried up via blogs.